Comparison of the Performance of Broiler Chickens Fed Swamp Water Treated with Alum Plus Chlorine, and Chitosan: Perbandingan Performa Ayam Broiler yang Diberi Air Rawa yang Diolah Menggunakan Tawas Plus Kaporit dengan Khitosan - Urip Santoso; Bieng Brata; Kususiyah Kususiyah; Sandrina Sandrina (BPFP Universitas Bengkulu, 2026)
This study aimed to evaluate the use of chemically treated and naturally treated swamp water on broiler chicken performance. Two hundred broiler chickens were distributed into 4 treatments with 5 replications as follows; P0: = swamp water was settled for 24 hours, P1 = swamp water was settled for 24 hours then treated with 24 mg/l chlorine and 24 mg/l alum, P2 = swamp water was settled for 24 hours then treated with 48 mg/l chitosan, and P3 = swamp water was settled for 24 hours then treated with 48 mg/l chitosan and filtered with a commercial filter. The results showed that the treatment had no significant effect (P>0.05) on drinking water consumption, feed intake, body weight, body weight gain, and feed conversion of broiler chickens. Based on the results of this study, it can be concluded that the use of chitosan in swamp water treatment tends to improve broiler chicken performance. Swamp water treatment in this study was not able to meet the feed intake standards for broilers.